What factors are important to parents making decisions about neonatal research?. Issue 3 (21st April 2005) - Hoehn, K S; Wernovsky, G; Rychik, J; Gaynor, J W; Spray, T L; Feudtner, C; Nelson, R M
Abstract : Background: Although parents of neonates with congenital heart disease are often asked permission for their neonates to participate in research studies, little is known about the factors parents consider when making these decisions. Objective: To determine the reasons for parents' decisions about participation in research studies. Methods: Qualitative analysis of the unsolicited comments of 34 parents regarding reasons for agreeing or declining to participate in research studies. Parents' comments were offered spontaneously during interviews about clinical care decisions for neonates with congenital heart disease. Results: Parents cited five types of reason for or against permitting their newborn to participate in research studies: societal benefit (n = 18), individual benefit for their infant (n = 16), risk of study participation (n = 10), perception that participation posed no harm (n = 9), and anti-experimentation views (n = 4). Conclusion: Addressing parental decision making in the light of these reasons could enhance the parental permission process for parents of critically ill neonates.